Modern technologies in solving design ideas - Katruha, Viktoriia; Tynynyka, Anastasiia (Professional Art Education, 2023)
Object. The article examines the role of modern technologies, which help design ideas to be implemented more effectively. The research aims to analyze and evaluate the use of artificial intelligence, virtual reality, 3D modeling, plug-ins and other advanced technologies in design, as well as to determine their impact on creativity, efficiency and sustainability of design solutions.Methods & methodology. During the scientific research, the methods of literary and scientific review, comparison and synthesis, analysis of existing computer programs and technologies were used.The scientific novelty of this article is revealed in an in-depth analysis of the impact of modern technologies on the processes of creation and development of design ideas through the use of artificial intelligence, virtual reality, 3D modeling, plugins and other advanced technologies, as well as in the determination of their impact on creativity, efficiency and sustainability of design solutions.Results. It has been determined that modern technologies, including artificial intelligence, virtual reality, 3D modeling, plug-ins and other innovative tools, have a significant impact on graphic design and open up endless possibilities for it. Artificial intelligence helps to automate and optimize the processes of working with graphics, creating personalized content and analyzing graphic trends. Virtual reality can significantly expand the possibilities of visualization and interaction with graphic objects. 3D modeling and 3D printing allow you to create realistic prototypes and products. Plugins have been proven to expand the functionality of graphics programs and simplify routine tasks. However, the use of these technologies also requires designers to improve their professional skills. It is emphasized that it is important to maintain a balance between the use of technologies and the creativity of the designer himself.Conclusions. The analysis of scientific articles and the contribution of scientists and practitioners in relation to the defined research problem was carried out. Programs and methods of creating a comfortable work process for the fastest and highest quality result are highlighted. Artificial intelligence, plug-ins, and neural networks are considered as auxiliary means. The work presents examples of such plugins for various programs and substantiates the principles of their use for the purpose of creating a design project and advertising one's own author's ideas. An attempt was made to analyze the prospects of using artificial intelligence in comparison with human capabilities within the framework of creating and improving the implementation of design projects, taking into account all the nuances and privileges.
Keywords: : design ideas; technologies; artificial intelligence; programs; 3D modeling; 3D printing